2000
DOI: 10.1093/jn/130.9.2274
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Ratio of (n-6)/(n-3) Polyunsaturated Fatty Acids Alters the Fatty Acid Composition of Bone Compartments and Biomarkers of Bone Formation in Rats

Abstract: The effects of dietary polyunsaturated fatty acids (PUFA) on ex vivo bone prostaglandin E(2) (PGE(2)) production and bone formation rate were evaluated in rats. Weanling male Sprague-Dawley rats were fed AIN-93G diet containing 70 g/kg of added fat for 42 d. The dietary lipid treatments were formulated with safflower oil and menhaden oil to provide the following ratios of (n-6)/(n-3) fatty acids: 23.8 (SMI), 9.8 (SMII), 2.6 (SMIII), and 1.2 (SMIV). Ex vivo PGE(2) production in liver homogenates and bone organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
211
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(239 citation statements)
references
References 42 publications
21
211
1
5
Order By: Relevance
“…Nutrition, including dietary fat, is related to molecular markers of bone remodeling and may contribute to the risk of bone-related diseases, which is supported by our findings (Watkins et al 2000;Seibel 2002). Several genes studied were significantly different between HFD and ND rats, a result supporting the findings of Xiao et al (2010Xiao et al ( , 2011 analyzing the gene expression between male mice fed HFD or ND.…”
Section: Discussionsupporting
confidence: 83%
“…Nutrition, including dietary fat, is related to molecular markers of bone remodeling and may contribute to the risk of bone-related diseases, which is supported by our findings (Watkins et al 2000;Seibel 2002). Several genes studied were significantly different between HFD and ND rats, a result supporting the findings of Xiao et al (2010Xiao et al ( , 2011 analyzing the gene expression between male mice fed HFD or ND.…”
Section: Discussionsupporting
confidence: 83%
“…Recent investigations indicate that the type and amount of PUFA influence bone formation and osteoblastic cell functions (Watkins et al, 2003), with evidence of an adverse effect for omega-6 PUFA (Watkins et al, 2000;Macdonald et al, 2004). Also, the intake of omega-6 fatty acids has been previously shown to be associated with a lower bone mineral density, and a high ratio of omega-6 to omega-3 has been reported to be detrimental for bone formation (Albertazzi and Coupland, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of PUFAs might be exerted via modulation and reduction of PGE 2 synthesis, reducing inflammation and affecting ALP activity [2,59].…”
Section: Figurementioning
confidence: 99%
“…PGE 2 also promotes the expression of various IGF-binding proteins [77,80,82] suggesting that PGE 2 could keep IGF available for stimulation of osteoblasts at a later phase of bone remodeling [77]. McCarthy et al [48] suggested that the ability of PGE 2 to enhance osteoblastic IGF-I synthesis could explain its anabolic potential, and furthermore suggests a role for PGE 2 in coupled bone remodeling. The anabolic effects of PGE 2 may occur through stimulation of endogenous IGF-I production by osteoblasts [83] or by increased bone cell responsiveness to IGF-I [84].…”
Section: Effects Of Dietary Polyunsaturated Fatty Acids and Their Promentioning
confidence: 99%
See 1 more Smart Citation